Response of five shallot varieties applied with Bacillus spp. against twisted disease - Pratiwi, Annisa Hasta; Wibowo, Arif; Joko, Tri; Widiastuti, Ani; Subandiyah, Siti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
The use of several shallot varieties applied with the biological agent Bacillus spp. is one of the most developed methods of controlling twisted disease, as it is safe and efficient. The large number of shallot varieties released to farmers requires the selection of varieties with the best resistance response to twisted disease. This study aimed to determine the different responses between five local shallot varieties treated with a combination of Bacillus velezensis B-27 and B. cereus RC76 against the twisted disease. This study was conducted in a greenhouse and on the field using Tajuk, Bima Brebes, Bauji, Crok Kuning, and Manjung varieties, which were dipped and sprayed with a B. velezensis B-27 and B. cereus RC76. The treatment of B. velezensis B-27 and B. cereus RC76 on five varieties showed a good response to suppressing twisted disease. The twisted disease incubation period in five varieties treated with the combination of B. velezensis B-27 and B. cereus RC76 showed a slower result than the control, the disease incidence and intensity could be reduced by 70 90%. The best resistance response of varieties treated with the combination of B. velezensis B-27 and B. cereus RC76 was shown by Tajuk compared to the other four varieties.